2012
DOI: 10.1016/j.ijgo.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary incontinence among Saudi women

Abstract: Female UI is prevalent in Saudi Arabia; however, the majority of women with this condition did not seek medical advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
57
3
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 25 publications
18
57
3
2
Order By: Relevance
“…8,11,12 Different studies have found a significant relationship between a history of pelvic surgery and UI, which is consistent with the result of the current study. [9][10][11] The limitations of the present study were as follows: there was no validated instrument to detect prevalence rates of UI in Kurdish women, the prevalence of UI was not studied in one specific age group, and UI was not studied in relation to obesity. Further studies should be conducted to test these important correlations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…8,11,12 Different studies have found a significant relationship between a history of pelvic surgery and UI, which is consistent with the result of the current study. [9][10][11] The limitations of the present study were as follows: there was no validated instrument to detect prevalence rates of UI in Kurdish women, the prevalence of UI was not studied in one specific age group, and UI was not studied in relation to obesity. Further studies should be conducted to test these important correlations.…”
Section: Discussionsupporting
confidence: 92%
“…20 In the current study, there was a significant association between UI and DM, chronic cough, and constipation which is consistent with the results of other studies. 11 SUI is triggered by physical exertion, including coughing, sneezing, straining, or exercise. In women, a weakness in the pelvic floor muscles, due to vaginal childbirth, may cause a defect in the support of the internal sphincter, ultimately leading to SUI.…”
Section: Discussionmentioning
confidence: 99%
“…[8,11,15] Bizim çalışmamızda doğum şekli ister vajinal, ister sezaryen olsun doğum yapmanın UI için risk faktörü olduğunu gözledik. Altintas ve ark.…”
Section: Discussionunclassified
“…23,24 Most of other studies in which stress insentience was commonest type. 25,26 In our study, the total prevalence of OAB was 39%. Of these 50.1% (176) reported that their sexual life is spoilt by OABS, 16.8% (59) of the women had to restrict their daily activities, 37.0% (130) reported their OABS affected their physical activities and 54.4% (191) said they affected their social life.…”
mentioning
confidence: 48%